2009
DOI: 10.1088/0029-5515/49/8/085037
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards a predictive model for pedestal height in DIII-D

Abstract: Abstract. Recent DIII-D pedestal studies provide improved characterization of pedestal scaling for comparison with models. A new pedestal model accurately predicts the maximum achieved pedestal width and height in TYPE-I ELMing discharges over a large range of DIII-D operational space, including ITER demonstration discharges. The model is a combination of the peeling-ballooning theory for the MHD stability limits on the pedestal with a simple empirical pedestal width scaling, which is proportional to the squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
92
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 40 publications
(104 reference statements)
19
92
0
Order By: Relevance
“…For this purpose, time windows with constant plasma parameters have been selected from a series of reproducible shots. The results show similar trends to those observed on AUG 11 and DIII-D 35,45 . In particular, they indicate that the pedestal pressure gradient may saturate shortly before the ELM onset.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For this purpose, time windows with constant plasma parameters have been selected from a series of reproducible shots. The results show similar trends to those observed on AUG 11 and DIII-D 35,45 . In particular, they indicate that the pedestal pressure gradient may saturate shortly before the ELM onset.…”
Section: Discussionsupporting
confidence: 84%
“…Some ELMs were directly triggered when the pressure gradient attained a critical value imposed by ideal MHD 5,44 . However, in other cases it has been observed that the pedestal remains at the pressure limit for several milliseconds before an ELM occurs 31,35 . Fig.…”
Section: A Type I Elmsmentioning
confidence: 99%
“…80, where the pedestal width is plotted as a function of the pedestal poloidal b. 232 The NSTX pedestal width follows a D ¼ c(b h ped ) 1 dependence, which is quite different from the D ¼ c 0 (b h ped ) 0.5 scaling for MAST 230 and DIII-D. 233 The $1.0 exponent scaling observed for NSTX has been shown to be consistent with preliminary analyses using the ballooning critical technique (BCP), 234 which yielded a 0.8 exponent scaling of the pedestal width as shown in Fig. 80.…”
Section: H-mode Pedestal and Edge Localized Modes (Elms)mentioning
confidence: 98%
“…In the region of the H-mode pedestal, unlike in the N 2.8 cases, there is a systematic increase of the width of the J BS peak in the pedestal region with increasing q 95 that results primarily from an increase in the width of the electron and ion density gradient profiles. These profile width increases may be the result of increased p [35].…”
Section: Bootstrap Current Densitymentioning
confidence: 99%